Ghrelin level and types of eating behavior when combined with irritable bowel syndrome, arterial hypertension and obesity - Vasyl G. MISCHUK; Galina V. GRYGORUK; Hanna Y. STUPNYTSKA; Rostislav Dm. LEVCHUK (Archives of the Balkan Medical Union, 2018)
Introduction. Regulation of gastrointestinal motility and eating behavior is one of the well‑known ghrelin’s effects. However, its cardioprotective effect, as well as vasodilatory action and participation in arterial pressure regulation, are not sufficiently studied.